Inhibition of transcription by dactinomycin reveals a new characteristic of immunogenic cell stress - Juliette Humeau; Allan Sauvat; Giulia Cerrato; Wei Xie; Friedemann Loos; Francesca Iannantuoni; Lucillia Bezu; Sarah Lévesque; Juliette Paillet; Jonathan Pol; Marion Leduc; Laurence Zitvogel; et al. (EMBO Molecular Medicine)
Abstract Chemotherapy still constitutes the standard of care for the treatment of most neoplastic diseases. Certain chemotherapeutics from the oncological armamentarium are able to trigger pre‐mortem stress signals that lead to immunogenic cell death (ICD), thus inducing an antitumor immune response and mediating long‐term tumor growth reduction. Here, we used an established model, built on artificial intelligence to identify, among a library of 50,000 compounds, anticancer agents that, based on their molecular descriptors, were predicted to induce ICD. This algorithm led us to the identification of dactinomycin (DACT, best known as actinomycin D), a highly potent cytotoxicant and ICD inducer that mediates immune‐dependent anticancer effects in vivo. Since DACT is commonly used as an inhibitor of DNA to RNA transcription, we investigated whether other experimentally established or algorithm‐selected, clinically employed ICD inducers would share this characteristic. As a common leitmotif, a panel of pharmacological ICD stimulators inhibited transcription and secondarily translation. These results establish the inhibition of RNA synthesis as an initial event for ICD induction.